Effectiveness and Clinical Value of Laparoscopic Cholecystectomy and Cholangiography in the Diagnosis of Biliary Calculi - Zhao, Yunqing; Tao, Hongbo; Liu, Yanqin; Sha, Gen; Yi, Xianyun; Qin, Qin; Jin, Dong; He, Chengjie; Wu, Xianghong; Zhou, Qing (Frontiers in Surgery, 2022)
Objective: To investigate the effectiveness and clinical value of cholangiography in the diagnosis of bile duct stones in laparoscopic cholecystectomy. Methods: 200 patients who underwent laparoscopic cholecystectomy in our hospital were randomly divided into research group and control group, with 100 cases in each group. The research group underwent choledochotomy and exploration with the help of choledochoscope, while the control group underwent cholangiography to diagnose bile duct stones. The cure rate, residual stone rate, complication rate, intraoperative bleeding, hospital stay and patient satisfaction were compared between the two groups. Results: in the control group, 9 cases were converted to laparotomy, 20 cases of common bile duct stones, 10 cases of bile duct injury and 6 cases of common bile duct variation. In the research group, there were 2 cases of conversion to laparotomy, 12 cases of common bile duct stones, 2 cases of bile duct injury and 4 cases of common bile duct variation. The cure rate of the researchgroup was higher than that of the control group, There was significant difference between the two groups (P < 0.05). The residual amount of stones in the research group was lower than that in the control group, and there was significant difference between the two groups (P < 0.05). The incidence of postoperative complications in the research group was lower than that in the control group, and there was significant difference between the two groups (P<0.05). The patient satisfaction in the research group was higher than that in the control group, and there was significant difference between the two groups (P < 0.05). The intraoperative blood output of the research group was lower than that of the observation group, and there was significant difference between the two groups (P<0.05). Conclusion: cholangiography is an effective method for the diagnosis of bile duct stones in laparoscopic cholecystectomy. Clarifying the variation and anatomical structure of bile duct is helpful to improve the surgical cure rate, reduce the residual rate of postoperative stones and the incidence of complications, reduce the amount of intraoperative bleeding, shorten the hospital stay, and promote the postoperative rehabilitation of patients.